Carta de Roberto H. Todd a Luis Muñoz Morales - Todd, Roberto H.; Muñoz Morales, Luis (My University, 1948)
Embarque de Romualdo Palacio y situación de Hernández López.
Keywords: Palacios, Romualdo; Hernández López, Juan; Contreras, Juan; Cabo, Segundo; Muñoz Morales, Luis--Correspondence.; Muñoz Morales, Luis--Correspondencia.; Todd, Roberto H.--Correspondence.; Todd, Roberto H.--Correspondencia.